Parent-of-origin effects orchestrate transcriptional reprogramming and epigenetic regulation of seedling vigor heterosis in triploid loquat - Zhang, Chi; Yuan, Ting; Guo, Shiqi; Dang, Jiangbo; Liang, Guolu; Gou, Xiuhong; Guo, Qigao; Wu, Di (Frontiers in Plant Science, 2025)
Triploid breeding is a promising avenue for generating seedless varieties with enhanced vigor, yet the underlying molecular mechanisms, particularly the relative contributions of hybridity, ploidy level, and parent-of-origin effects (POE), remain largely elusive in perennial fruit crops. This study focuses on loquat (Eriobotrya japonica), a highly heterozygous woody perennial, to explore the molecular mechanism of triploid seedling vigor heterosis. RNA-seq across a series of reciprocal diploid (2x), triploid (3x) and tetraploid (4x) hybrids with clear genetic background revealed POE as the predominant driver of triploid heterosis at the transcriptomic level. Specifically, 784 POE-responsive differentially expressed genes (DEGs) were identified between paternal-excess [3x(p)] and maternal-excess [3x(m)] triploids, exceeding the effects of ploidy (218–652 DEGs) and hybridity (8–90 DEGs). For an in-depth investigation, reciprocal crosses between L2 and L4 were further selected for an integrated transcriptome, allele-specific expression (ASE), and allele-specific methylation (ASM) analysis. Our findings demonstrate that POE orchestrates multilayered regulation, including (i) coordinated upregulation of vigor-related pathways (i.e., photosynthesis, starch metabolism, plant circadian rhythm) in 3x(p); (ii) a dual ASE pattern with maternal bias in gene quantity but paternal enhancement in levels, including five paternally expressed imprinted genes (PEGs); (iii) non-classical epigenetic regulation where paternal gene body hypermethylation (mCG) paradoxically enhances transcription, especially in circadian clock genes. Finally, qRT-PCR-based diurnal expression across all crosses validated that POE-dependent reprogramming of key circadian oscillator genes (EjCCA1, EjLHY, EjGI, EjTOC1), suggesting optimized metabolic efficiency through circadian clock modulation might contribute to enhanced vigor in 3x(p) hybrids. This study provides fundamental insights into the dosage-sensitive gene networks and epigenetic regulation underlying POE-driven heterosis in woody perennials, advancing polyploid heterosis theory and offering novel targets for genetic improvement.